Trends in School Science Laboratory Management in the 21st Century: Literature Review on the Role of Digitalization, Safety, and Independent Curriculum - Alifia Dwi Anggraini; Hamdi Akhsan; Iful Amri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Management of Natural Sciences (Science) laboratories in 21st century schools faces challenges in implementing digitalization, enforcing security standards, and adapting to the Independent Curriculum. This article aims to analyze literature related to the role of digitalization, safety aspects, and adaptation of the Independent Curriculum in science laboratory management. The method used is literature study from various trusted sources. The research results show that digitalization of science laboratories can increase the efficiency and effectiveness of learning, but requires increased teacher competency and adequate infrastructure. Apart from that, work safety standards in laboratories still need to be considered, including training for teachers and students. Implementing the Independent Curriculum requires adjustments in laboratory management to support more flexible and project-based learning. In conclusion, effective science laboratory management in the digital era requires technology integration, implementation of safety standards, and adaptation to the Independent Curriculum, supported by adequate training and infrastructure